What if we get it right? : visions of climate futures - Johnson, Ayana Elizabeth (One World, 2024)
"Sometimes the bravest thing we can do while facing an existential crisis is imagine life on the other side. This provocative and joyous book maps an inspiring landscape of possible climate futures. Through clear-eyed essays and vibrant conversations, infused with data, poetry, and art, Ayana Elizabeth Johnson guides us through solutions and possibilities at the nexus of science, policy, culture, and justice. Visionary farmers and financiers, architects and advocates help us conjure a flourishing future, one worth the effort it will take-from all of us, with whatever we have to offer-to create. If you haven't yet been able to picture a transformed and replenished world-or see yourself, your loved ones, and your community in it- this book is for you. If you haven't yet found your role in shaping this new world, or you're not sure how we can actually get there, this book is for you. With grace, humor, and humanity, Ayana invites readers to ask and answer this ultimate question, together: What if we get it right?"--